Biotin and chromium histidinate improve glucose metabolism and proteins expression levels of IRS-1, PPAR-?, and NF-?B in exercise-trained rats - Turgut, Mine; Cinar, Vedat; Pala, Ragip; Tuzcu, Mehmet; Orhan, Cemal; Telceken, Hafize; Şahin, Kazım (Taylor & Francis Inc, 2018)
Background: Chromium histidinate (CrHis) and biotin are micronutrients commonly used to improve health by athletes and control glycaemia by patients with diabetes. This study investigates the effects of 8-week regular exercise training in rats together with dietary CrHis and biotin supplementation on glucose, lipids and transaminases levels, as well as protein expression levels of peroxisome proliferator-activated receptor gamma (PPAR-gamma), insulin receptor substrate-1 (IRS-1) and nuclear transcription factor kappa B (NF-kappa B). Methods: A total of 56 male Wistar rats were randomly divided into 8 groups of 7 animals each and treated as follows: Control, CrHis, Biotin, CrHis+Biotin, Exercise, CrHis+Exercise, Biotin+Exercise, and CrHis+Biotin+Exercise. The doses of CrHis and biotin were 400 pg/kg and 6 mg/kg of diet, respectively. The training program consisted of running at 30 m/ min for 30 min/day at 0% grade level, 5 days per week, once a day for 6 weeks. Serum glucose, total cholesterol (TC), high-density lipoprotein cholesterol (HDL), triglycerides (TG), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were measured with an automatic biochemical analyzer. Muscle and liver PPAR-gamma, IRS-1 and NF-kappa B expressions were detected with real-time polymerase chain reaction. Results: Regular exercise significantly (p < 0.001) decreased glucose, IC and TG levels, but increased HDL cholesterol. Dietary CrHis and biotin supplementation exhibited a significant (p < 0.001) decrease in glucose (effect size = large; eta 2 = 0.773) and TG (effect size = large; eta 2 = 0.802) levels, and increase in HDL cholesterol compared with the exercise group. No significant change in AST and ALT (effect size = none) levels was recorded in all groups (p > 0.05). CrHis/biotin improves the proteins expression levels of IRS-1, PPAR-gamma, and NF-kappa B (effect size: large for all) in the liver and muscle of sedentary and regular exercise-trained rats (p < 0.001). Conclusions: CrHis/biotin supplementation improved serum glucose and lipid levels as well as proteins expression levels of PPAR-gamma, IRS-1 and NF-kappa B in the liver and muscle of exercise-trained rats, with the highest efficiency when administered together. CrHis/biotin may represent an effective nutritional therapy to improve health.
Keywords: Chromium Histidinate; Biotin; PPAR-gamma; IRS-1; NF-kappa B